Key components of working capital management: investment performance in Malaysia - Loo, Pui Yan; Lau, Wei Theng (Growing Science, 2019)
This study attempts to examine the role of working capital management components on four commons which are distinctive dimensions of business investment performance in Malaysia. The analysis covers 431 listed companies for the period 2000-2017 post the Asian financial crisis. The four performance indicators are return on assets (to proxy book return on overall business assets), return on equity (to proxy book return on shareholders’ fund), Tobin’s Q (to proxy firm valuation) and stock performance (to proxy real shareholder wealth). Our results indicate that working capital components of receivables collection period, inventory conversion period, payables deferral period, overall cash conversion cycle, current ratio, quick ratio, and cash ratio have generally exhibited important relationships with investment performance before and after the 2007-2008 subprime crisis. We would like to highlight the very robust negative effect of receivables collection period and cash conversion cycle. In addition, it is worth noting the distinctive roles of cash conversion cycle components and working capital liquidity ratios. While overly high liquidity position is usually viewed as inefficiency and detrimental for profitability, our panel data analysis consistently show that a high liquid position is favourable if the impact of cash conversion cycle is well considered. Hence, it is crucial for managers to prioritize the importance of working capital requirements to enhance the value of investors.